Discrimination of saccharides by a simple array - Bojanowski, Maximilian; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F. (Chemistry - a European journal, 2017)
We report the development of a two-component probe system as fluorescence turn-on assay of simple saccharides. The quenching of an anionic conjugated water-soluble polymer by a cationic quencher has been reported previously. Three different boronic acid functionalized benzyl viologens and three conjugated polymers of the poly(aryleneethynylene) type form nine non-fluorescent complexes. This small library discriminates nine different simple saccharides in aqueous solutions by fluorescence turn-on in a displacement assay. The saccharides can be discriminated and identified with this simple system.